1984
DOI: 10.1007/bf00396772
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic interactions in an aphid-host plant relationship: Uroleucon rudbeckiae and Rudbeckia laciniata

Abstract: Four clones of the aphid Uroleucon rudbeckiae were grown on four clones of the host plant Rudbeckia laciniata. Age-specific fecundities were used to determine the fitness, F' , of each individual aphid. The analysis of variance for F' revealed that (1) plant genotype has a significant effect on aphid fitness; (2) there is an interaction between aphid and host plant genotypes with respect to aphid fitness; and (3) aphid fitness is affected by phenotypic differences among individual host plants. Result (2) suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…It has also been demonstrated that within-species genetic variation is important for directly interacting species (Service 1984, Mopper 1996, and the effect can be mediated by the presence or absence of a third species in the community (Tetard-Jones et al 2007). Thus, there is clear evidence showing that genetic variation within a species will affect directly interacting species; however, we do not know to what extent genetic variation, and genotypic interactions, within intermediate species will affect the outcome of indirect interactions.…”
Section: Introductionmentioning
confidence: 97%
“…It has also been demonstrated that within-species genetic variation is important for directly interacting species (Service 1984, Mopper 1996, and the effect can be mediated by the presence or absence of a third species in the community (Tetard-Jones et al 2007). Thus, there is clear evidence showing that genetic variation within a species will affect directly interacting species; however, we do not know to what extent genetic variation, and genotypic interactions, within intermediate species will affect the outcome of indirect interactions.…”
Section: Introductionmentioning
confidence: 97%
“…Factors 2-4 are also major assumptions of local mate competition models. Several studies have demonstrated that plant genotypes vary in their suitability for insect growth and reproduction (e.g., Marquis, 1984;Moran, 1981;Service, I984a). Environmental variation also affects plant phenotype in ways that influence insect fitness (Rausher, 1981;Service, 1984b).…”
mentioning
confidence: 99%
“…Previous work has demonstrated that genetically based interactions between species can influence the phenotypes of both the directly and indirectly interacting individuals (Service 1984;Carius et al 2001;Tétard-Jones et al 2007;Zytynska et al 2010). For example, the indirect effect of a soil rhizobacteria on the body-size (fitness) of a parasitoid wasp was mediated by genotypic interactions between the linking barley and aphid species (Zytynska et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Genetic interactions between different species also occur, which can influence the fitness of the species involved. For example, genotypic interactions between an aphid (Uroleucon rudbeckiae) and its herbaceous perennial host plant (Rudbeckia laciniata) influenced aphid reproductive rate (Service 1984). Such interactions have also been shown to occur in hostparasite systems (e.g.…”
Section: Introductionmentioning
confidence: 98%